First do no harm - Rozan, S. J. (Rozan, S. J. Lydia Chin/Bill Smith novels., 2026)
"With River Valley Hospital in the midst of negotiations to avert a nurses' strike, a wealthy benefactor is set to give a large donation to honor the Chief of Emergency Medicine: Dr. Elliott Chin, the brother of private investigator Lydia Chin. Before the donation can be finalized, a member of the nurses' negotiating committee is found murdered. A morgue assistant is arrested, and although he denies even knowing the victim, his father and brother--both doctors at the hospital--are quick to urge him to take a plea. Another negotiating committee member abruptly resigns and a senior biomedical technician disappears. An officially off-limits section of the hospital basement turns out to be a hotbed of unauthorized--and in some cases criminal--activity. Hired by the arrested man's lawyer, Lydia Chin and her partner Bill Smith start to dig into the events and personnel at the hospital"--